EKSISTENSI BI'AH LUGHAWIYAH DI DAYAH TERPADU AL-MUSLIMUN LHOKSUKON ACEH UTARA - Mohd. Nasir Mukhlis, Meutia Rahmah (Ihya al-Arabiyah: Jurnal Pendidikan Bahasa dan Sastra Arab, 2016)
Environment has important role in obtaining language, although in natural or un natural environment. Learning foreign language, needed to form unnatural environment, so the student easy to learn it well. Boarding school is a place to create the unnatural environment, is one of integrated boarding in Aceh which apply "bi'ah lughawiyah" (language environment). When other boarding school didn't perform the bi'ah yet, in this boarding school the bi'ah lughawiyah  performed well. The purpose of this writing is to know how "bi'ah lughawiyah" can be exist in this boarding and obstacles that will be faced. By direct observing, interview and FGD so can be concluded that Dayah Boarding School Al-Muslim Lhoksukon Aceh Utara can be exist because it is supported by English-arabic learning method which are variative, innovative and fun. Without applying physicall punishment, it must be educative using religion approach if it is applied such as saying istighfar. It is supported by media of learning, eventhough it was not complete yet, it can be maximal. Endorsement of appropriate curriculum gives effect in topic. Moreever the provide of human resourch in speaking English-Arabic of  institution and director that have positive effect to existence of bi'ah lughawiyah in boarding school Al-Muslim Lhoksukon. The obstacle which is faced in existence the bi'ah lughawiyah in boarding school Al-Muslimun lhoksukon it is only minor obstacle, students who break discipline/disobey of language. Kata Kunci : Bi'ah Lughawiyah, Eksistensi